Hitler’s Ethic - Weikart, R. author. aut Link
XIII, 254 p.
Keywords: In this book, Weikart helps unlock the mystery of Hitler's evil by vividly demonstrating the surprising conclusion that Hitler's immorality flowed from a coherent ethic. Hitler was inspired by evolutionary ethics to pursue the utopian project of biologically improving the human race.